Can CRISPR/Cas Technology Be a Felicitous Stratagem Against the COVID-19 Fiasco? Prospects and Hitches - Konwarh, Rocktotpal (Frontiers in Molecular Biosciences, 2020)
The current global debacle of COVID-19, spelled by SARS-CoV-2 needs no elaboration. With incessant and constantly clambering number of deaths across various nations, the need of the hour is to develop readily deployable, fast, affordable detection assays and kits, yielding precise and consistent results as well as opportune availability of efficacious anti-SARS-CoV-2 strategies to contain it. Conventionally employed real time PCR based technique for detection of the virus suffers from a couple of handicaps. Amongst other approaches, CRISPR based technology has ushered in new hopes. Recent efforts have been directed towards developing CRISPR/Cas based low-cost, rapid detection methods as well as development of one-pot assay platforms. The plausible application of CRISPR-Cas system to counteract the viral assault has also been assessed. The write up in this article mirrors the prospects, limitations and current status of CRISPR/Cas based technology to diagnose and address viral infections as in the current COVID-19 catastrophe.